A Differentiated Approach to the Asset-Light Model in the Hotel Industry. (August 2022) - Märklin, Paulina; Bianchi, Giuliano
This research note aims to prompt a debate over the asset-light strategy that hotels are increasingly implementing nowadays. First, it evaluates the impact of an asset-light model on hotel firms' returns, return volatility, and the Sharpe ratio, based on annual data from 1970 to 2018 of 65 U.S. public hotel firms. Evidence shows that going asset-light has no significant impact on companies' returns, return volatility, and performance. Second, the study offers possible explanations behind such results and raises questions for future research.